2018
DOI: 10.1063/1.5026186
|View full text |Cite
|
Sign up to set email alerts
|

Electron acoustic nonlinear structures in planetary magnetospheres

Abstract: In this paper, we have studied linear and nonlinear propagation of electron acoustic waves (EAWs) comprising cold and hot populations in which the ions form the neutralizing background. The hot electrons have been assumed to follow the generalized (r,q) distribution which has the advantage that it mimics most of the distribution functions observed in space plasmas. Interestingly, it has been found that unlike Maxwellian and kappa distributions, the electron acoustic waves admit not only rarefactive structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…16,18,25 These nonthermal distributions significantly deviate from the classical Maxwellian distribution function and have successfully been employed to investigate different kinds of phenomena in realistic environments. 13,14,16,17,[26][27][28] In this paper, we use generalized (r,q) distribution function to study the nonlinear ion-acoustic waves which has the following standard three-dimensional form 18 f rq (…”
Section: Model Formalismmentioning
confidence: 99%
“…16,18,25 These nonthermal distributions significantly deviate from the classical Maxwellian distribution function and have successfully been employed to investigate different kinds of phenomena in realistic environments. 13,14,16,17,[26][27][28] In this paper, we use generalized (r,q) distribution function to study the nonlinear ion-acoustic waves which has the following standard three-dimensional form 18 f rq (…”
Section: Model Formalismmentioning
confidence: 99%
“…Whenever particle distribution has an abundance of superthermal particles, it is modelled in a better fashion by employing kappa distribution function. [36] This aspect could not be investigated by distributions containing high-energy tails only. Tahir et al [25] employed bi-product (r, q) distribution for adiabatically trapped electrons to study obliquely propagating Alfven waves.…”
Section: Introductionmentioning
confidence: 99%
“…Electrons are assumed to follow the (r, q) distribution function for which the total electron density can be written as [22,36] n e = (1 +…”
Section: Model Equationsmentioning
confidence: 99%
“…Several studies on non-Maxwellian plasmas have shown that wave characteristics change significantly due to the presence of non-thermal distributions and provided a better insight into the underlying physical processes. [22][23][24][25][26] Kappa distribution has been used extensively to study various electrostatic and electromagnetic non-linear waves in astrophysical and space plasmas and is characterized by the spectral index , which basically models the particles with velocities greater than the thermal velocity. A smaller value of signifies a larger number of high-energy particles in the distribution and vice versa.…”
Section: Introductionmentioning
confidence: 99%